Treatment of cardiac sarcoidosis: A comparative study of steroids and steroids plus immunosuppressive drugs. (1st February 2019) - Ballul, Thomas; Borie, Raphael; Crestani, Bruno; Daugas, Eric; Descamps, Vincent; Dieude, Philippe; Dossier, Antoine; Extramiana, Fabrice; van Gysel, Damien; Papo, Thomas; Sacre, Karim
Abstract: Background: We aimed to compare the efficacy of steroids alone or associated with immunosuppressive drugs for the prevention of relapse in cardiac sarcoidosis (CS). Methods: In this monocentric multidisciplinary retrospective single center study, all consecutive patients with histologically proven sarcoidosis hospitalized from January 2012 to December 2016 were considered. All patients with symptomatic CS were studied. Patients received steroids or steroids plus immunosuppressive drugs (IS) for CS treatment at diagnosis. The efficacy of each treatment strategy (steroids vs steroids + IS) was assessed by the cardiac relapse rate over follow up. Results: 326 consecutive patients with histologically proven sarcoidosis were screened. Among them, 36 (11%) had symptomatic CS (20 (55.5%) men, median age at diagnosis 48.5 [22.8–76]). Twenty-four patients received steroids and 12 received steroids + IS (azathioprine n = 5, methotrexate n = 5, cyclophosphamide n = 2) at CS diagnosis. Over a median follow up of 3.6 [1–15.2] years, 13 (36.1%) patients suffered a cardiac relapse including reduced left ventricular ejection fraction (LVEF, n = 4), third degree heart block (n = 2), atrio-ventricular (n = 1) or ventricular (n = 1) tachycardia and sudden cardiac death (n = 1). Except for a higher frequency of black patients in patients receiving IS, CS features at diagnosis and median time to relapse did not significantly differ between patients who did or did not receive IS. Relapse rate was 45.8% in the steroids group versus 16.7% in the steroids + IS group (p = 0.048). Conclusions: In cardiac sarcoidosis, the combination of steroids with immunosuppressive drugs might reduce the risk of cardiac relapse, as compared to steroids alone. Highlights: Heart involvement is the leading cause of death in sarcoidosis Evidence-based data regarding cardiac sarcoidosis treatment are poor Steroids and immunosuppressive drugs may be more effective than steroids alone in preventing cardiac sarcoidosis relapse.